2010
DOI: 10.1590/s0104-11692010000400021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Smoking in Pregnancy

Abstract: The aim of this cross-sectional study was to identify factors related to smoking during pregnancy. The sample included 267 puerperae hospitalized in the maternity unit of a university hospital in Porto Alegre/RS. The data were collected through a self-applied instrument and statistically analyzed. The majority of the puerperae (51.3%) were between 18 and 25 years old, 55.4% were nonsmokers, 25.5% were smokers, 19.1% had recently ceased smoking (in abstinence). The nonsmokers had more consultations than the smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
3
16
0
6
Order By: Relevance
“…Others may be encouraged to quit smoking, through concerted counseling about the risks of smoking to fetus and mother that begins at the initiation of prenatal care [18]. On the whole, pregnant women are receptive to educational measures and health promotion [17] and are more likely to consider smoking cessation in the context of the frequent contact with health professionals during prenatal care [9]. Accordingly, the prenatal protocol of the Brazilian Health Ministry [16] instructs that smoking pregnant women be identified in prenatal medical visits, advised to quit and offered support to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others may be encouraged to quit smoking, through concerted counseling about the risks of smoking to fetus and mother that begins at the initiation of prenatal care [18]. On the whole, pregnant women are receptive to educational measures and health promotion [17] and are more likely to consider smoking cessation in the context of the frequent contact with health professionals during prenatal care [9]. Accordingly, the prenatal protocol of the Brazilian Health Ministry [16] instructs that smoking pregnant women be identified in prenatal medical visits, advised to quit and offered support to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarettes are among the most frequently used drugs in pregnancy [9]. A Brazilian study identified greater chance of smoking during pregnancy in women with a higher number of previous pregnancies and who did not undergo prenatal care [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents mentioned emotional state, addiction to cigarettes, experiencing pleasure in smoking and influence of others, more specific, of a smoking partner, as factors that hinder smoking cessation. This study, however, was not carried out in pregnant women, but took place between 24 and 48 hours after birth [9]. Smoking pregnant women reported significantly higher scores on a depression scale [Beck Depression Inventory (BDI) scale] compared with non‐smoking pregnant women [10].…”
Section: Introductionmentioning
confidence: 99%
“…A violência física mostrou associação com o tabagismo da mulher durante a gestação, o que pode ter algumas interpretações como uma possível perda da autoestima que leva a mulher a adquirir comportamentos de risco, como o hábito de fumar para aliviar o estresse e o sofrimento causados pela violência (16), assim como a convivência com parceiros tabagistas exercendo uma importante influência quanto a não cessação do hábito durante a gestação (17). Lembrando que as associações aqui encontradas não podem ser consideradas uma relação de causa e efeito, devido o delineamento do estudo.…”
Section: Discussionunclassified